Experimental study on the dynamic mechanical properties of concrete under freeze–thaw cycles. (10th May 2018) - Han, Nv; Tian, Wei
Abstract : This study investigated the dynamic mechanical properties of concrete subjected to freeze–thaw cycles. Freeze–thaw cycle experiments were carried out using a freeze–thaw tester to vary the temperature from 20 ± 2 °C to −20 ± 2 °C, from 0 to 100 cycles. Uniaxial compression tests were performed with a tested strain rate ranging from 1.0 × 10 −5 /s to 1.0 × 10 −2 /s using a servo‐hydraulic testing machine. Dynamic compressive strengths were measured and the effects of freeze–thaw cycles and strain rates were investigated. The experimental results suggested that the dynamic compressive strength of specimens generally decreased as the number of freeze–thaw cycles increased, and the dynamic compressive strength was significantly affected by strain rates. The dynamic compressive strength of concrete and the dynamic increase factor both increased with increased strain rate. X‐ray computed tomography scanning was used to study the strain‐rate effects on internal structure damage in the specimens. Cracks propagated along two different paths, passing along the aggregate–mortar interfaces and passing through the aggregates along the failure surfaces.